Global burden and health inequality of atrial fibrillation/atrial flutter from 1990 to 2021 - Li, Xia; Li, Zhen; He, Hongtao; Wang, Sizhou; Su, Honglei; Kang, Guobin (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAtrial fibrillation (AF) and atrial flutter (AFL) are the most prevalent tachyarrhythmias worldwide, leading to severe complications such as stroke and heart failure. Despite advancements in diagnosis and management, the global burden of AF/AFL continues to increase, highlighting the urgent need for comprehensive epidemiological research.MethodsThis study analyzed data from the Global Burden of Disease (GBD) 2021 to examine the incidence, prevalence, mortality, and disability-adjusted life years (DALYs) associated with AF/AFL from 1990 to 2021. Age-standardized rates were calculated at global, regional, and country-specific levels. Decomposition and Bayesian age-period-cohort models were used to explore trends and forecast future disease burdens.ResultsIn 2021, AF/AFL contributed to 4.48 million new cases globally, with an age-standardized incidence rate (ASIR) of 52.1 per 100,000. The global prevalence reached 52.55 million cases, while the disease caused 338,947 deaths. The global age-standardized DALY rate stood at 101.4 per 100,000. Significant disparities were observed, with higher disease burdens in high Socio-demographic Index (SDI) regions compared to low SDI regions. Between 1990 and 2021, aging and population growth were key drivers of the increased burden, with regional variations associated with economic development and healthcare access. Bayesian projections indicate a gradual rise in incidence and prevalence through 2050, although mortality and DALY rates are expected to decline.ConclusionsAF/AFL presents a substantial public health challenge, with rising incidence and prevalence primarily driven by demographic changes and enhanced diagnostic capabilities. Addressing health inequalities requires targeted interventions and strengthening healthcare systems. Future strategies should prioritize prevention and equitable access to advanced therapies.